Improved charge separation efficiency of hematite photoanodes by coating an ultrathin p-type LaFeO3 overlayer. (7th September 2017) - Fang, Tao; Guo, Yongsheng; Cai, Songhua; Zhang, Ningsi; Hu, Yingfei; Zhang, Shiying; Li, Zhaosheng; Zou, Zhigang
Abstract: Many metal-oxide candidates for photoelectrochemical water splitting exhibit localized small polaron carrier conduction. Especially hematite ( α -Fe2 O3 ) photoanodes often suffer from low carrier mobility, which causes the serious bulk electron-hole recombination and greatly limits their PEC performances. In this study, the charge separation efficiency of hematite was enhanced greatly by coating an ultrathin p-type LaFeO3 overlayer. Compared to the hematite photoanodes, the solar water splitting photocurrent of the Fe2 O3 /LaFeO3 n–p junction exhibits a 90% increase at 1.23 V versus the reversible hydrogen electrode, due to enlarging the band bending and expanding the depletion layer.